Anti-ulcer activity of leaves and bark of ficus racemosa linn in ethanol & aspirin induced ulcer in rats - Singh, Divyash (International Journal of Pharmaceutical & Biological Archive, 2017)
Aim- The main of aim of study was to evaluate the Anti-ulcer activity of various extracts of leaves & bark of Ficus racemosa in Animals. Material & Methods-The crude drugs were extracted out by using various non polar and polar solvents and preliminary phytochemical screening were performed for the presence of different phytocompounds. Ethanol & Aspirin induced ulcer model was used for the experiment & treatment of different Polar & Non Polar extracts of Leaves & barks of Ficus racemosa in animals were given. Results- On the comparisons from results, it was found that methanolic extract (200 & 400 mg/kg) of bark of Ficus racemosa showed highly significant activity (p<0.001) on % protection against ulcer formation in ethanol and aspirin induced models.